A Paradigm of Learning: What Teachers Should Know about Students - Larry Martin (Educational Considerations, 1975)
Teachers have to be able to answer why a child is having learning problems before they can decide how they can help. Project HELP, an in-service teacher training program, was designed to aid teachers in their search for the reason why children have learning problems.